Cefepime Neurotoxicity in Patients With Normal Renal Function: An Overlooked Cause of Encephalopathy in the Intensive Care Unit - Zakaria Alagha MD, MSc; Samuel Crow MSc; Abdul Muhsen Z. Abdeen MD; Maha Alastal MD; Amro Alastal MD, FACP, FCCP (SAGE Publishing, 2024)
Cefepime is a fourth-generation cephalosporin with extended antimicrobial coverage. Concerns have been raised about the side effects of cefepime including myoclonus, encephalopathy, and seizures, especially when renal impairment is present. There have been reports of cases of adverse neurological consequences despite appropriate renal adjustment. Here, we present a case of a 69-year-old patient initially diagnosed with pneumonia and treated with cefepime. The patient later developed altered mental status, leading to differential diagnoses including stroke, drug overdose, or non-convulsive seizures. Following a comprehensive workup, it was determined that she had cefepime-induced encephalopathy, despite having normal kidney function, which resolved completely after discontinuing the medication. In addition, we include similar cases retrieved from PubMed up to the present date, to the best of our knowledge.